IMPLEMENTASI KEBIJAKAN STANDAR NASIONAL PENDIDIKAN (SNP) PADA SEKOLAH DASAR NEGERI NO.68 DI KECAMATAN PONTIANAK BARAT KOTA PONTIANAK - Febriyani E.01108066, Unggi (PublikA, Jurnal Ilmu Administrasi Negara, 2012)
AbstractThe title of research is Implementation Standar National Education Policy at elementaryschool number 68, in West Pontianak, Pontianak. The purpose of this research to know whatthe problems implementation standar national Education policy that to do in the schoolincrease several graduate not yet reached standar school grades to made government and thefuture this implementation can get result graduate good academic value then reached purposestandar national education policy. The method of this research is descriptive and thetechnique is qualitative data analysis. In this research standar national education on standarprocess that including planning process, learning process and good example. The result pfdata analysis show the always have new regulation policy and different every time until needunderstanding and adjust with planning before, minimum infrastructure, and there are teachercann’t make a good example to pupils.Keywords : implementation policy, planning process, learning process and good example